Impact of Spironolactone on Longitudinal Changes in Health-Related Quality of Life in the Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist Trial. (March 2016) - Lewis, Eldrin F.; Kim, Hae-Young; Claggett, Brian; Spertus, John; Heitner, John F.; Assmann, Susan F.; Kenwood, Christopher T.; Solomon, Scott D.; Desai, Akshay S.; Fang, James C.; McKinlay, Sonia A.; Pitt, Bertram A.; et al.
Abstract : Background—: Heart failure (HF) with preserved ejection fraction patients have equally impaired health-related quality of life (HRQL) compared with those with HF with reduced ejection fraction, but limited studies have evaluated the impact of therapies on changes in HRQL. Methods and Results—: Patients ≥50 years of age, with symptomatic HF and left ventricular ejection fraction ≥45%, were enrolled in Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist (TOPCAT) and randomized to spironolactone or placebo. Patients completed the Kansas City Cardiomyopathy Questionnaire (KCCQ), which was the primary HRQL instrument, and EQ5D visual analog scale at baseline, 4 months, 12 months, and annually thereafter. McMaster Overall Treatment Evaluation was assessed at 4 and 12 months to assess global change scores. Change scores (+SD) were calculated to determine between-group differences, and multivariable repeated-measures models were created to identify other factors associated with change scores. Paired KCCQ data were available for 91.7% of 3445 TOPCAT patients. By 4 months, the mean change in KCCQ was 7.7±16 and mean change in EQ5D visual analog scale was 4.7±16. Adjusted mean changes in KCCQ for the spironolactone group were significantly better than those for the placebo group at 4-month (1.54 better; P =0.002), 12-month (1.35 better; P =0.02), and 36-month (1.86 better; P =0.02) visits. No between-group differences in EQ5D visual analog scale change scores or McMaster Overall Treatment Evaluation were noted. Older age, obesity, current smoking, New York Heart Association class III/IV, and comorbid illnesses were associated with declines in KCCQ scores. Use of spironolactone was an independent predictor of improved KCCQ scores. Conclusions—: In symptomatic HF with preserved ejection fraction patients, use of spironolactone was associated with an improvement in HF-specific HRQL. Several modifiable risk factors were associated with HRQL deterioration. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00094302. Abstract : Supplemental Digital Content is available in the text.